Investigation of obesity-related HAdV-36 in NAFLD patients: A case-control study - Dinç, Harika Öykü; Çizmecigil, Utku; Sulu, Cem; Yıldırım, Süleyman; Turgut, Başar C.; Sirekbasan, Serhat; Aydoğan, Okan; Durman, Tunahan; Özbey, Doğukan; Aslan, Beyza; Sonsuz, Abdullah; Zengin, Kağan; et al. (Verlag Klinisches Labor GmbH, 2023)
Background: HAdV-36 leads to adipocyte proliferation of adipose tissue through E4orf1 gene, leading to the development of obesity and related diseases. We aimed to investigate the presence and any association of HAdV-36 in non-alcoholic fatty liver disease (NAFLD) patients Methods: The patient group was composed of 116 patients; 30 obese patients with NAFLD (BMI > 30 kg/m2), 30 patients with Diabetes Mellitus (DM)+NAFLD (BMI > 30 kg/m2), 16 patients with NAFLD (BMI < 30 kg/m2), and operated obese group with NAFLD (BMI > 30 kg/m2). The control group comprised 81 non-obese healthy adults. Liver adipose tissue samples were obtained in 30 operated NAFLD patients. HAdV-36-DNA, HAdV-36 neutralizing antibodies, serum lipid, and adipokine levels were analyzed. Results: HAdV-36 neutralizing antibodies (HAdV-36 Ab-positive) were detected in 10/116 and 2/81 participants in the study and control groups, respectively; the difference was statistically significant (p < 0.005). LDL, total cholesterol but not adipokine levels were found to be significantly higher in HadV-36 Ab-positive patients (p < 0.05). While HAdV-36 was identified as a risk factor with OR = 4.11 in univariate analyses, there was no significant difference in binary logistic regression analysis. HAdV-36-DNA was detected in the adipose tissue samples of two patients. Conclusions: We suggest that the presence of HAdV-36 may lead to the development of obesity with the increase in adipose tissue, and diseases such as hyperlipidemia, NAFLD, DM, and metabolic syndrome may develop on the basis of chronic inflammation caused by obesity. Thus, HAdV-36 may be a plausible risk factor for the development of NAFLD.
Keywords: HAdV-36; HAdV-36 DNA; NAFLD; Obesity; Serum Neutralizing